Pemanfaatan Koleksi Grey Literature Di Perpustakaan Politeknik Wilmar Bisnis Indonesia (WBI) Skripsi - Daulay, Ardiani; Batubara, Abdul Karim; Yusniah, Yusniah (CV. ITTC INDONESIA, 2024)
This research discusses the utilization of grey literature collection at Wilmar Bisnis Indonesia (WBI) Polytechnic Library. This study aims to determine the use of grey literature collections in the Wilmar Bisnis Indonesia Politechnic (WBI) library and to determine the obstacles experienced by users in utilizing grey literature collections in the P-WBI library. This Type of research is descriptive with a qualitative approach. Data collection techniques in this study used observation, interviews an documentation. While the data analysis techniques in this study are data reduction, data presentation and conclusions. This research was conducted at the Wilmar Bisnis Indonesia Polytechnic library. The result of this study show that the use of grey literature collections in the library is well utulized by users in their daily activities to find reference materials to fulfill college assignments or student final projects. The obstacles experienced by users in utilizing grey literature collections are unstable conditions of information accessibility, completeness of collections and disorganization of documents or collections